2020
DOI: 10.1101/2020.11.08.373399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drought shifts sorghum root metabolite and microbiome profiles and enriches the stress response factor pipecolic acid

Abstract: Interactions between plants and their root-associated microbiome are important for determining host fitness during periods of stress. During drought, monoderm bacteria are more abundant in sorghum roots than in those of watered controls. Additionally, a reversion from monoderm to diderm dominance occurs in drought-stressed roots one week after rewatering. However, the mechanisms driving this rapid microbiome composition shift is currently unknown. To understand if changes in host metabolism are correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…However few studies have identified changes of rhizosphere metabolites in soil in response to abiotic stressors. For example, Caddell et al 2021 investigated the dynamics of sorghum rhizosphere metabolites during drought (87), and Mavrodi et al (2012) established that phenazines accumulate in the rhizosphere of dryland cereals (88), but responses to nutrient limitation, in particular, have been understudied in rhizosphere soil. Here, we demonstrate that metabolites recovered from the rhizosphere soil of switchgrass shifted in response to nutrient (N, P) and water-limited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However few studies have identified changes of rhizosphere metabolites in soil in response to abiotic stressors. For example, Caddell et al 2021 investigated the dynamics of sorghum rhizosphere metabolites during drought (87), and Mavrodi et al (2012) established that phenazines accumulate in the rhizosphere of dryland cereals (88), but responses to nutrient limitation, in particular, have been understudied in rhizosphere soil. Here, we demonstrate that metabolites recovered from the rhizosphere soil of switchgrass shifted in response to nutrient (N, P) and water-limited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate the carbon sources available in the sorghum rhizosphere, a new media recipe was designed based on previously reported metabolomics analysis of the rhizosphere soil of sorghum grown plants (Caddell et al, 2020). The base formula represents a MOPS Media Enhanced (MME) solution, to which a select group of carbon and nitrogen sources were added.…”
Section: Ssm Media Formulationmentioning
confidence: 99%
“…These processes are orchestrated by multilayer components involving plants, microorganisms, soil, and environmental traits that shape the final result. The accumulation of stress-related factors in plant roots during drought, including G3P and pipecolic acid, has been linked to actinobacteria enrichment in the rhizosphere (Knight et al, 2018;Caddell et al, 2020; Table 2).…”
Section: Plant-mediated Reshaping Of Microbiota Composition In Respon...mentioning
confidence: 99%